Organocatalytic Packed-Bed Reactors for the Enantioselective Flow Synthesis of Quaternary Isotetronic Acids by Direct Aldol Reactions of Pyruvates - Lorenzo Poletti; Carmela De Risi; Daniele Ragno; Graziano Di Carmine; Riccardo Tassoni; Alessandro Massi; Paolo Dambruoso (Molecules)
The utilization of the homogeneous (S)-2-pyrrolidine-tetrazole organocatalyst (Ley catalyst) in the self-condensation of ethyl pyruvate and cross-aldol reactions of ethyl pyruvate donor with non-enolizable pyruvate acceptors, namely the sterically hindered ethyl 3-methyl-2-oxobutyrate or the highly electrophilic methyl 3,3,3-trifluoropyruvate, is described as the key enantioselective step toward the synthesis of the corresponding biologically relevant isotetronic acids featuring a quaternary carbon functionalized with ester and alkyl groups. The transition from homogeneous to heterogeneous flow conditions is also investigated, detailing the fabrication and operation of packed-bed reactors filled with a silica-supported version of the pyrrolidine-tetrazole catalyst (SBA-15 as the matrix).